An Organometallic Gold(I) Bis‐N‐Heterocyclic Carbene Complex with Multimodal Activity in Ovarian Cancer Cells. Issue 67 (3rd November 2020) - Meier‐Menches, Samuel M.; Neuditschko, Benjamin; Zappe, Katja; Schaier, Martin; Gerner, Marlene C.; Schmetterer, Klaus G.; Del Favero, Giorgia; Bonsignore, Riccardo; Cichna‐Markl, Margit; Koellensperger, Gunda; Casini, Angela; Gerner, Christopher
Abstract: The organometallic Au I bis‐N‐heterocyclic carbene complex [Au(9‐methylcaffeine‐8‐ylidene)2 ] + (AuTMX2 ) was previously shown to selectively and potently stabilise telomeric DNA G‐quadruplex (G4) structures. This study sheds light on the molecular reactivity and mode of action of AuTMX2 in the cellular context using mass spectrometry‐based methods, including shotgun proteomics in A2780 ovarian cancer cells. In contrast to other metal‐based anticancer agents, this organogold compound is less prone to form coordinative bonds with biological nucleophiles and is expected to exert its drug effects mainly by non‐covalent interactions. Global protein expression changes of treated cancer cells revealed a multimodal mode of action of AuTMX2 by alterations in the nucleolus, telomeres, actin stress‐fibres and stress‐responses, which were further supported by pharmacological assays, fluorescence microscopy and cellular accumulation experiments. Proteomic data are available via ProteomeXchange with identifier PXD020560. Abstract : Golden touch : A cationic organometallic gold(I) complex featuring N‐heterocyclic carbene ligands and endowed with selective anticancer activity towards human ovarian A2780 cancer cells was studied using an integrated investigational approach, including shotgun proteomics, mass spectrometry and pharmacological methods. The obtained results suggest a multimodal activity related to actin stress fibres, Nrf2‐mediated redox response and telomere disturbance.